Penerapan Sistem Akuntansi Keuangan Desa (SISKEUDES) Dalam Transparansi Dan Akuntabilitas Pengelolaan Dana Desa : Studi Kasus Kecamatan Huristak Kabupaten Padang Lawas - Roslinda Harahap; Fauzi Arif Lubis; Rahmat Daim Harahap (BADAN PENERBIT STIEPARI PRESS, 2023)
This study aims to determine the application of the village financial accounting system in the transparency and accountability of village fund management and the constraints in its application in Huristak District, Padang Lawas Regency. The village financial accounting system is an application developed by BPKP in order to improve the quality of village financial governance that is accountable and transparent. This study uses a descriptive qualitative approach. Sources of data obtained from primary data and secondary data collected by researchers by observing and interviewing techniques, and reviewing the literature related to the village financial accounting system in the transparency and accountability of village fund management. The results of this study concluded that the application of the village financial system in the transparency and accountability of managing village funds in the Huristak sub-district cannot be said to be effective and successful in its implementation due to the lack of human resources (HR) in the Huristak sub-district government. However, the application of the siskeudes application can increase transparency and accountability to the public for their financial reports even though they are still assisted by village assistants.